A session allocation algorithm for switch with multiple shared output links; The 1st International Conference on Information Technology, november 28-30, Suwon, Korea, 2003 - Shim Jaehong; Jung Gihyun; Jang Joongsoon; Alkhimov Yu. V. Yuri Vasilyevich; Choi Kyunghee (2003, 2003)
В фонде НТБ ТПУ отсутствует